2019
DOI: 10.5539/sar.v8n3p66
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Endophyte Detection Techniques in Grasses

Abstract: Endophytes are the plant mutualists that live asymptomatically inside plant tissue and are found in nearly whole plant kingdom. Endophytic fungi receive shelter and nutrition from host plants and in return provide great advantages to the host. Grasses are a useful forage species and are of great agricultural and socio-economic value. The presence of endophytes in these grasses provide protection, persistence and improved yield against herbivores, insects, pathogens, drought and several other biotic and abiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…That lives within a host on specific host part or cell, without causing apparent disease. According to Ahmad et al [6] It live asymptomatically inside plant tissue and found the most plant kingdom. The symbiont of endophyte and plant are mostly mutualism, where each species has a net benefit.…”
Section: Resultsmentioning
confidence: 99%
“…That lives within a host on specific host part or cell, without causing apparent disease. According to Ahmad et al [6] It live asymptomatically inside plant tissue and found the most plant kingdom. The symbiont of endophyte and plant are mostly mutualism, where each species has a net benefit.…”
Section: Resultsmentioning
confidence: 99%
“…Various techniques for detecting fungal pathogens in their respective host plants are discussed in the literature ( Ahmad et al, 2019 ). Some basic traditional and biochemical techniques are used to detect R. solani and diagnose the diseases caused by Rhizoctonia species, particularly in legumes are shown Table 2 .…”
Section: Detection and Diagnostic Approaches For Rhizoctoni...mentioning
confidence: 99%
“…Methods to determine endophyte presence within a plant include microscopy, immunoblot tissue print testing, and polymerase chain reaction (PCR) testing for endophyte‐derived molecular markers (Ahmad et al, 2019) and a plate‐based assay, enzyme‐linked immunosorbent assay. High‐performance liquid chromatography can be used to identify alkaloid content (Hiatt et al, 1999).…”
Section: Introductionmentioning
confidence: 99%